STUDI DESKRIPTIF PEMAHAMAN MAHASISWI ANGKATAN 26 TENTANG KARAKTER WANITA SALEH BERDASARKAN KITAB RUT DI SEKOLAH TINGGI TEOLOGI KRISTUS ALFA OMEGA SEMARANG. - Margareth Christin haba Soulissa; Ragil Kristiawan; Gidion Gidion (STT Kristus Alfa Omega, 2020)
Students of class 26 in Alfa Omega Semarang Theological College of Semarang has an incomplete understanding about the Character of Virtuous Women which brings impact on their behavior and some of them didn’t carry out their obligations as Christian women. Therefore, this research is done to know their understanding level about the character of godly women according to the Book of Ruth in Alfa Omega Semarang Theological College of Semarang. This research use quantitative method of descriptive type. The understanding level of 26th female college about the character of godly women according to the Book of Ruth in Alfa Omega Semarang Theological College of Semarang categorized as high level.